Experimental transmission of Caryospora kutzeri (Apicomplexa: Eimeriidae) by rodent hosts - Volf, Jiří; Modrý, David; Koudela, Břetislav (Folia Parasitologica)
Four laboratory-hatched European kestrels Falco tinnunculus L. were fed on laboratory mice and common voles Microtus arvalis Pallas previously inoculated with different doses of sporulated oocysts of Caryospora kutzeri Böer, 1982. Two kestrels that were fed infected mice shed C. kutzeri oocysts 6 days after ingesting murine tissues. To compare direct and indirect transmissions, two of the kestrels were subsequently directly inoculated with 105 sporulated C. kutzeri oocysts and became patent on days 8 and 9 and shed caryosporan oocysts up to day 25 post inoculation. Additionally, four mice were inoculated with 106 oocysts in order to examine mouse tissues for the presence of developmental stages of C. kutzeri. No coccidian stages were found in the tissues of inoculated mice. The experiment showed that developmental stages of C. kutzeri are able to survive in mouse tissues and cause infection of suitable host after their ingestion.